2003
DOI: 10.1038/nn1016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic balance of metabotropic inputs causes dorsal horn neurons to switch functional states

Abstract: Sensory relay structures in the spinal cord dorsal horn are now thought to be active processing structures that function before supraspinal sensory integration. Dorsal horn neurons directly receive nociceptive (pain) signals from the periphery, express a high degree of functional plasticity and are involved in long-term sensitization and chronic pain. We show here that deep dorsal horn neurons (DHNs) in Wistar rats can switch their intrinsic firing properties from tonic to plateau or endogenous bursting patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 49 publications
13
107
0
Order By: Relevance
“…Ruscheweyh and Sandkuhler (2002) found comparable cell types in lamina I, and other studies have described similar cell types in deeper spinal laminas (Thomson et al, 1989;Yoshimura and Jessell, 1989;Lopez-Garcia and King, 1994;Jo et al, 1998;Grudt and Perl, 2002;Schneider, 2003). The diversity of intrinsic cellular properties allows for a wealth of computational processes influencing transmission of sensory information through the dorsal horn (Morisset and Nagy, 1998;Russo and Hounsgaard, 1999;Derjean et al, 2003). However, processing that occurs in lamina I and its biophysical basis remain poorly understood.…”
Section: Introductionmentioning
confidence: 74%
“…Ruscheweyh and Sandkuhler (2002) found comparable cell types in lamina I, and other studies have described similar cell types in deeper spinal laminas (Thomson et al, 1989;Yoshimura and Jessell, 1989;Lopez-Garcia and King, 1994;Jo et al, 1998;Grudt and Perl, 2002;Schneider, 2003). The diversity of intrinsic cellular properties allows for a wealth of computational processes influencing transmission of sensory information through the dorsal horn (Morisset and Nagy, 1998;Russo and Hounsgaard, 1999;Derjean et al, 2003). However, processing that occurs in lamina I and its biophysical basis remain poorly understood.…”
Section: Introductionmentioning
confidence: 74%
“…In trigeminal and hypoglossal motoneurons, inward depolarizing currents from N-and P-type calcium channels, along with a TTX-sensitive current, have been identified as additional sources of depolarizing currents along with the L-type calcium current (Hsiao et al 1998;Powers and Binder 2003). Some of these depolarizing currents originate from the dendritic tree (Bennett et al 1998;Carlin et al 2000;Lee et al 2003;Powers and Binder 2003 (Derjean et al 2003;Hounsgaard and Kjaerulff 1992;Russo and Hounsgaard 1996), no evidence of such currents has been found in Renshaw cells. An immunohistochemical study found on average, 4 serotonergic boutons on cat Renshaw cells (Carr et al 1999), confirming earlier reports that unlike for motoneurons, serotonin has a weak effect on Renshaw cells.…”
Section: Physiological Implicationsmentioning
confidence: 98%
“…Rhythmic bursting activity is a characteristic feature of central pattern generators (CPGs) that drive rhythmic behaviors (Kiehn et al 2000;Marder and Calabrese 1996) and is involved in the transmission of sensory information (Derjean et al 2003;Krahe and Gabbiani 2004), in the formation and retrieval of memories (Lisman 1997;Pike et al 1999), and in other fundamental functions of nervous systems. In CPGs and other bursting networks, the burst period, consisting of the burst duration and the interburst interval, can be modified according to functional demands, such as locomotor speed, by altering the interburst interval (see e.g., Sorensen et al 2004) and/or the burst duration.…”
Section: Introductionmentioning
confidence: 99%